TOWARDS SUSTAINABLE EVENT PLANNING: CURRENT STATE OF PLAY, BEST PRACTICES, AND CHALLENGES CREATING SUSTAINABLE EVENTS - Nusa Lazar (Agora International Journal of Economical Sciences (AIJES), 2023)
The topic of sustainability has gained widespread acceptance in many areas of society, with significant claims for the benefits of adopting the principles of sustainability in business and management. According to the United Nations, a sustainable event is one designed and organized to meet two main objectives: to minimize all potential negative impacts on the environment and leave a beneficial legacy for the host community and all involved. In the last few years, the concept of sustainable event planning has been incorporated also into the event industry, turning the attention of event management to issues of environment, social, and governance (ESG) as well as diversity, equity, and inclusion (DEI). The author will elaborate on the current state of sustainable event planning, outline some best practices in this sector, and deriving from the results of different studies make recommendations as to how the industry can and should make sustainability core to activities in event management.
Keywords: 330